Pengaruh Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada Apron Movement Control (AMC) PT. Angkasa Pura I Bandar Udara Internasional Yogyakarta - Mellan Maula Trisanti; Eka Prayudista (Jurnal Bintang Manajemen, 2023)
ABSTRACT , The working relationship of employees and leaders can determine the level, benefits of the Work Environment and Employee Performance of the company they feel. Any positive work relationship can help create a healthy work environment and environment for employees. The purpose of this research is to find out how the work environment affects the work productivity of employees at the AMC Unit of PT. Angkasa Pura I Yogyakarta International Airport. This study used a quantitative method with data collection techniques through questionnaires and documentation which was carried out from 1 March to 31 March 2023. Respondents from this study were all employees of AMC PT. Angkasa Pura I Yogyakarta International Airport with a total of 15 people. testing the results of this research using IBM SPSS 23 Statistics For Windows. The results showed that variable X (Work Environment) on variable Y (Employee Performance) in the AMC Unit with a simple linear regression test showed a strong influence by obtaining a correlation coefficient of 0.576 and a large effect with a coefficient of determination test of 33.1%. Therefore, the work environment must be maintained or improved so that the performance of the AMC Unit personnel of PT. Angkasa Pura I at Yogyakarta International Airport maintains and improves its performance in the room and in the field.